Professions and (new) management occupations as a contested terrain: Redefining jurisdictional claims. Issue 3 (31st October 2018) - Heusinkveld, Stefan; Gabbioneta, Claudia; Werr, Andreas; Sturdy, Andrew
ABSTRACT: In this article, we discuss how research on professions and organizations may benefit from a better understanding of the emergence and prevalence of 'new' management occupations or 'corporate professions' and their interactions with 'traditional' professions. To this end, we explore the theoretical and empirical implications of selected studies, analysing how professional and occupational jurisdictions, as well as inter-occupational relationships, are redefined . This occurs as new areas of management expertise emerge and gain influence in relation to broader organizational, technical and institutional developments.